The Influence of Work Conflict on Employee Voice Behavior: Self-Efficacy as a Moderator - Lintang Dwi Saputri; Zainnur M. Rusdi; Dina Safitri (STIE Amkop Makassar, 2025)
This study aims to examine the influence of work conflict on employee voice behavior (EVB), with self-efficacy as a moderating variable, within the context of Indonesia’s manufacturing industry. Employing a quantitative approach with a causal research design, data were collected from 130 employees using a structured questionnaire. The findings reveal that both task and relationship conflicts do not significantly impact EVB. Analysis using Partial Least Square–Structural Equation Modeling (PLS-SEM) indicates that self-efficacy do not strengthens the relationship between work conflict and EVB. This research contributes theoretically by integrating social exchange theory and social cognitive theory, while also offering practical implications for human resource management strategies to enhance employee participation in organizational decision-making.